Improving the pedagogic competence of physical education teachers - Tri Ani Hastuti; Soegiyanto Soegiyanto; Wawan Sundawan Suherman; Setya Rahayu; Nur Sita Utami (Jurnal Cakrawala Pendidikan, 2022)
The competencies possessed by teachers have not been as expected, as evidenced by the average value of pedagogic competencies, which are still low compared to the results of professional competence scores on the Teacher Competency Test. This study aimed to develop a model for improving the pedagogic competence of Physical Education teachers which was arranged into a module that contains how to develop a learning implementation plan, how to create and use the learning media, how to create and use the teaching materials, and how to prepare and implement the learning assessments. The development tests that were carried out were: 1) alpha test, 2) beta test, and 3) final product validation. The alpha test is a product validation test by three experts, while the beta test is a load and product suitability test involving 27 teachers and 3 supervisors, followed by a final product validation stage involving 84 teachers who are divided into two groups, namely experimental and control. The research instruments used were a questionnaire and a competency improvement scale. The data analysis techniques used are quantitative descriptive data analysis, gain score data analysis, and t-test. Based on the results of the assessment at the alpha test, beta test, and program validation stages, the resulting product was declared suitable for use as a teaching material set. Furthermore, through the process of testing the effectiveness of the product, the model of increasing pedagogic competence based on teaching materials is proven to be effective and can significantly improve the pedagogic competence of Physical Education teachers.